Gestión del conocimiento administrativo y su impacto en el desarrollo profesional de las secretarias en la secretaría general de la facultad de ciencias de la salud - Junco Tapia, Ángel Armando (2020)
The human being habitually makes different advances and innovations and it is through the investigation that allows to facilitate passage to different scopes and theories, the recent case study contributes to the training for the management of the central registry and laying these of value for the institutions that seek to preserve an efficiency management, the same ones contributing to the administrative course a way to develop and obtain a high disposition model. In this case study to be able to acquire the indispensable investigation that gave me results in the future, I used the survey to obtain measures to the projected problem and through the inductive methodology I was able to clearly gather what the problem is in this faculty, I have to mention that any development for this part of the institution obtains a well-being and an improvement and in addition to this also the administrative knowledge of the Faculty in the secretaries of the different careers. The administrative management of an establishment is not easy work, but it is the secretaries who contribute to the development of this institution to support this work task, one of the activities that is the attention to the public is one of the most important jobs that the secretary has Since it is the essential of every institution for development and progress, for proper discernment all faculties should have a way of working with the attention of the public since they show the good result of the activities done in their functions, all agility increases to the business management and therefore will succeed, we secretaries are responsible for appropriating all kinds of steps that occur in the offices with due formality thinking that we must give a high increase to our entity.